A Sensitive Amperometric Sensor for the Determination of Sophocarpine Based on Vertically Oriented Graphene Nanosheets Modified Glassy Carbon Electrode. Issue 6 (1st January 2015) - Wang, Fei; Cao, Yi; Zhang, Bingying; Gao, Lin; Ge, Junda
Abstract : We presented to fabricate the electrodeposition of the film of reduced graphene oxide (ERGO) with preferred vertical orientation on the glassy carbon electrode through pulse potential method (PPM). The ERGO film were characterized by electrochemical methods and scanning electron microscopy. For the first time, the electrodeposition of the film was applied to develop a highly sensitive electrochemical sensor for determination of sophocarpine. The electrochemical behavior of sophocarpine was then studied by cyclic voltammetry. The results revealed that the ERGO film can effectively increase response toward the oxidation of sophocarpine by greatly enhancing the oxidation peak currents and decrease the overpotential of sophocarpine. Under the selected conditions, the sensor showed good amperometric response for sophocarpine within a wide linear range from 1.0 × 10 −6 to 1.0 × 10 −4 mol L −1 and a low detection limit of 3.0 × 10 −7 mol L −1 . At the same time, the method was also successfully applied to the quantitative determination of sophocarpine in spiked human urine and its result was satisfactory.